Whose voices? The fate of Luigi Nono’s 'Voci destroying muros' - Adlington, Robert (University of California Press, 2016)
Luigi Nono's Voci destroying muros for female voices and small orchestra was performed for the first and only time at the Holland Festival in 1970. A setting of texts by female prisoners and factory workers, it marks a sharp stylistic departure from Nono's political music of the 1960s by virtue of its audible quotations of revolutionary songs, its readily intelligible text setting, and especially its retention of the diatonic structure of the song on which the piece is based, the communist “Internationale.” Nono's decision, following the premiere, to withdraw the work from his catalogue suggests that he came to regard it as transgressing an important boundary in his engagement with “current reality.” I examine the work and its withdrawal in the context of discourses within the Italian left in the 1960s that accused the intellectuals of the Partito Comunista Italiano of unhelpfully mediating the class struggle. Nono's contentious reading of Antonio Gramsci, offered as justification for his avant-garde compositional style, certainly provided fuel for this critique. But Voci destroying muros suggests receptivity on the part of the composer—albeit only momentary—to achieving a more direct representation of the voices of the dispossessed.